Diabolism and Male Child Preference in the Cause of Mental Illnesses in Ebuka Onuma’s Film, Moment of Madness - Adjeketa, Blessing; Adjeketa, Theophilus (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This paper examines diabolism and male-child preference as the cause of mental illness in Moment of Madness, a Nollywood film. Mental illnesses have become like a cankerworm eating deep into the fabric of global societies. Places of treatment that patients' relatives choose for victims depend on the cause of the illness. Factors causing mental illnesses depicted in Nollywood are also under-studied. This paper uses Attribution theory and textual analysis methods to read the cause of mental illness in the film, Moment of Madness. The study exposes that Nollywood films set in traditional African society portray traditional causes like diabolic as one of the root causes of mental illnesses and male child preference as a leading factor for Charity’s use of diabolism to cause mental illness to Mmesoma in the film.